2022
DOI: 10.3389/fmicb.2022.989667
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon essential oil and its emulsion as efficient antibiofilm agents to combat Acinetobacter baumannii

Abstract: Acinetobacter baumannii is an emerging nosocomial pathogen resistant to a wide spectrum of antibiotics, with great potential to form a biofilm, which further aggravates treatment of infections caused by it. Therefore, searching for new potent agents that are efficient against A. baumannii seems to be a necessity. One of them, which has already been proven to possess a wide spectrum of biological activities, including antimicrobial effect, is cinnamon essential oil. Still, further increase of antibacterial effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Similar result was found for strains of P. aeruginosa , tested under the same conditions, showed different responses to the same EO ( Coseriu et al., 2023 ), corroborating the difficulty to treat this type of infection. Other studies have also showed significant antibacterial properties for cinnamon EO, which inhibited the growth of A. baumannii , P. aeruginosa and K. pneumoniae ( El-Kattan and Allam, 2021 ; Ganić et al., 2022 ; Coseriu et al., 2023 ). Furthermore, this EO exhibited higher antibiofilm activity against K. pneumoniae , followed by peppermint EO ( Sarwar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar result was found for strains of P. aeruginosa , tested under the same conditions, showed different responses to the same EO ( Coseriu et al., 2023 ), corroborating the difficulty to treat this type of infection. Other studies have also showed significant antibacterial properties for cinnamon EO, which inhibited the growth of A. baumannii , P. aeruginosa and K. pneumoniae ( El-Kattan and Allam, 2021 ; Ganić et al., 2022 ; Coseriu et al., 2023 ). Furthermore, this EO exhibited higher antibiofilm activity against K. pneumoniae , followed by peppermint EO ( Sarwar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…It was observed that the formulations that had cinnamon EO in their composition (F1, F6, F7 and F8) have showed activity against all the analysed strains/species and that the F1 formulation maintained in vitro antibacterial activity even after 1 year of storage at room temperature. Other work also revealed that the loaded cinnamon EO exhibited promising antibacterial activity and prevented both biofilm formation from A. baumannii strains, also exhibiting antibiofilm capacity ( Ganić et al., 2022 ). Another work described that the strains of P. aeruginosa also showed susceptibility to cinnamon EO at lowest concentrations, (0.125% v/v).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the same extract promoted a reduction of 67.17% of the clinical strain of A. baumannii A2, also with a similar action to chlorhexidine gluconate (79.22%). This may be explained by the cinnamon essential oil that acts to inhibit and eradicate the biofilm of clinical strains of A. baumannii with reductions of up to 71% of the biofilm formed at a concentration of 1 mg/mL [29].…”
Section: Discussionmentioning
confidence: 99%